KAJIAN NORMATIF PASAL 173 KOMPILASI HUKUM ISLAM DALAM PENERAPAN SYARIAT ISLAM (TATHBIQ AL-SYARIAH) - Zaida Hayati; Anwar Hafidzi (Makkah: Journal Of Islamic Studies, 2025)
This study examines the application of Islamic law principles in Article 173 of the Compilation of Islamic Law (KHI) regarding inheritance barriers (mawāni‘ al-irts) in the context of Islamic inheritance law in Indonesia. The purpose of this study is to analyze the Sharia basis, social relevance, and legal rationality of the expansion of inheritance barriers in Article 173 of the KHI through the ijtihad tathbîqî approach within the framework of tahqîq al-manâṭ. This study uses a literature review method with a normative juridical approach, accompanied by an analysis of shar‘i texts and contemporary social realities. The results of the study show that the expansion of mawāni‘ al-irts—which includes attempted murder, severe abuse, and slander against the heir—has shar‘i legitimacy through the stages of istinbâth min al-nushûsh, idrâk al-wâqi’, and tanzîl al-ahkâm, and is in line with maqāṣid al-syarī‘ah, particularly the protection of life and honor. In addition, this provision serves as a preventive measure through the application of the principle of sadd al-dzarî‘ah. Thus, Article 173 of the KHI represents a contextual and adaptive renewal of Islamic inheritance law to the needs of contemporary Indonesian society